Advanced Assessment Dynamics Neglected Age: Barriers and Skills Communication Worker Social in Bandung City Social Services - Tukino, Tukino (Journal of Ecohumanism, 2024)
Study This aiming For analyze dynamics in the assessment process of carry on elderly neglected in Bandung City Social Service, with focus on the barriers faced by workers social as well as skills necessary communication For overcome challenge The research method used is approach qualitative with technique data collection in the form of interview in-depth, observation, and study documentation. Research results show that Assessment is step important in practice worker social For understand problem client and determine appropriate interventions, especially for elderly displaced with dementia. However, this process face various obstacles, such as limitations cognitive, difficulties communication, change emotions, limitations physical, as well as obstacle culture and language. Elderly with dementia often difficulty give information accurate Because disturbance Power remember or difficulty speaking. In addition, workers social often faced with a lack of tool help communication and training special. Therefore that, skill communication become very important For overcome obstacle this, like ability do interview effective, listening active, and understanding non-verbal communication. Mastery technology supporter, understanding culture, as well as supervision and feedback return is also required For increase effectiveness assessment and support welfare elderly.